Creativity and Local Wisdom: Community Empowerment in Developing Traditions, Arts, and Culture in the Giyanti Wonosobo Hills Area in Central Java - Haryanto, Sri; Sukawi, Sukawi; Rozi, Fathur (Civiliza Publishing, 2024)
The community service program